ECONOMIC CONSEQUENCES OF TAX NONCOMPLIANCE - Heru Iswahyudi (Badan Pendidikan dan Pelatihan Keuangan - Kementerian Keuangan Republik Indonesia, 2018)
This paper aims to examine how tax noncompliance may affect capital accumulation and economic growth in Indonesia within the framework of endogenous growth theory. It is found that the economic effect of tax noncompliance may depend more on how the available capital is utilized, rather than its impact on capital accumulation per se. Empirical results also show that private investment has higher productivity than public investment. Further, it seems that the role of private investment in growth process is much larger and more important than public investment and these results are robust across several specifications. The central thesis of this paper is that expansionary fiscal policies may need to carefully consider the productivity constraints that might be faced by public sector investments.